New opportunities for applications of cellulose nanocrystal: non-covalent protein coupling analysis by flow cytometry - JULIANE C. GLÓRIA; LUIS ANDRÉ M. MARIÚBA; YURY O. CHAVES; ADÉLIA M. DE FIGUEIREDO; LIZANDRO MANZATO (Anais da Academia Brasileira de Ciências)
Abstract Cellulose nanocrystals (CNCs) are known for several features which make them one of the nanoparticles with great potential for application in different areas such as biosensors development and carrier molecules. However, there are few reports in the literature describing the coupling analysis of cellulose nanocrystals with biomolecules, and the existing ones are laborious, still needing a large laboratory structure. In this paper, we describe the non-covalent coupling of Bovine Serum Albumin protein (BSA) to CNCs using Green Fluorescent Protein (GFP) as a reporter molecule. Analyzes of these tests were performed using the flow cytometry technique. The nanocrystal particles became fully fluorescent when coupled to a concentration of 1 µg GFP. BSA coupling was able to block binding to GFP when at a concentration of 8 µg. Thus, flow cytometry has proven to be a simple and effective methodology for determining BSA coupling percentage to CNCs.